Examining Cross-Age Peer Conversations Relevant to Character: Can a Digital Story About Bullying Promote Students' Understanding of Humility?. Issue 2 (2nd April 2016) - Batanova, Milena; Bowers, Edmond P.; Hilliard, Lacey J.; Tirrell, Jonathan M.; Stacey, Danielle C.; McClain, AnneMarie; Lerner, Richard M.
Abstract : Successful character education programs are commonly marked by components including conversations about moral issues; however, little is known about what students actually talk about in such programs. Using initial data from the Arthur Interactive Media Buddy Project, this study examined whether a digital comic about bullying generated meaningful conversations surrounding humility. The sample was 52 cross-age peers in elementary school. Analyses involved an iterative, deductive-inductive coding process resulting in a total of ten codes, of which three were most readily identified in peers' conversations: perspective taking, affect labeling, and empathic responding. Limitations and implications relevant to character education are discussed.